The struggle for Palestinian hearts and minds: violence and public opinion in the second intifada - David A. Jaeger; Esteban F. Klor; Sami H. Miaari; Marco Daniele Paserman (Institute for the Study of Labor (IZA), 2008)
This paper examines how violence in the Second Intifada influences Palestinian public opinion. Using micro data from a series of opinion polls linked to data on fatalities, we find that Israeli violence against Palestinians leads them to support more radical factions and more radical attitudes towards the conflict. This effect is temporary, however, and vanishes completely within 90 days. We also find some evidence that Palestinian fatalities lead to the polarization of the population and to increased disaffection and a lack of support for any faction. Geographically proximate Palestinian fatalities have a larger effect than those that are distant, while Palestinian fatalities in targeted killings have a smaller effect relative to other fatalities. Although overall Israeli fatalities do not seem to affect Palestinian public opinion, when we divide those fatalities by the different factions claiming responsibility for them, we find some evidence that increased Israeli fatalities are effective in increasing support for the faction that claimed them.
urn:nbn:de:101:1-2008041432
Keywords: D72; 330; Israeli-Palestinian conflict; fatalities; public opinion; Politische Gewalt; Krieg; Öffentliche Meinung; Israel; Palästina